Perencanaan Sistem Penyediaan Air Minum Di Kecamatan Ukui, Kabupaten Pelalawan - Retno Dwi Pangastuti; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The people in Ukui District, Pelalawan Regency meet their drinking water needs from bottled water, dug wells, river water and springs based on the 2018 RPIJM Pelalawan Regency. The quality and quantity of drinking water has not been guaranteed. The need for water in Ukui District in 2019-2038 is 111.24 L / sec, so it is necessary to plan a drinking water supply system for the next 20 years. The transmission system that carries raw water comes from the Air Hitam River. Based on the mass balance analysis, it is found that units capable of treating raw water with water quality are in accordance with PERMENKES number 492 of 2010. The processing units are planned for intake, pre-sedimentation, neutralization, coagulation, flocculation, sedimentation, filtration, and disinfection. This plan is also equipped with supporting buildings, namely chemical buildings, water towers, sludge treatment units and office buildings. The drinking water supply system plans a drinking water distribution pipeline network made using EPANET 2.0 software, namely the main pipe network. The budget required for planning a drinking water supply system in Ukui District is Rp. 98,813,000,000, -.Keywords: Ukui, Air Hitam River, Water requirements, Unit Production, Piping, EPANET 2.0